The effects of 8 weeks of two different training methods on on-sight lead climbing performance - Philippe, M.; Filzwieser, I.; Leichtfried, V.; Blank, C.; Haslinger, S.; Fleckenstein, J.; Schobersberger, W. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Despite climbing being an increasingly popular sporting pursuit, there have been very few scientific evaluations of appropriate training methods for competitive climbers. The aim of this study was to investigate the effects of an 8-week climbing-specific muscular hypertrophy (MH) or muscular endurance (ME) resistance training program on the on-sight lead climbing performance in a similar setting to a World Cup.